2018
DOI: 10.1038/s41598-018-34619-w
|View full text |Cite
|
Sign up to set email alerts
|

A multiscale study of fungal endophyte communities of the foliar endosphere of native rubber trees in Eastern Amazon

Abstract: Hevea brasiliensis is a native hyperdiverse tree species in the Amazon basin with great economic importance since it produces the highest quality natural rubber. H. brasiliensis, in its natural habitat, may harbor fungal endophytes that help defend against phytopathogenic fungi. In this work, we investigated the fungal endophytic communities in two pristine areas in Eastern Amazon (Anavilhanas National Park – ANP and Caxiuanã National Forest – CNF) at different spatial scales: regional, local, individual (tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 57 publications
6
15
0
1
Order By: Relevance
“…T. harzianum HB324 was isolated by our research group from Hevea brasiliensis (rubber tree) leaves and our data have shown that this isolate can act as biocontrol agent against the phytopathogen Colletotrichum sp. (Fonseca et al, 2018). Despite the economic and ecological importance of this fungus, its mitochondrial genome has not been yet available.…”
Section: Discussionmentioning
confidence: 99%
“…T. harzianum HB324 was isolated by our research group from Hevea brasiliensis (rubber tree) leaves and our data have shown that this isolate can act as biocontrol agent against the phytopathogen Colletotrichum sp. (Fonseca et al, 2018). Despite the economic and ecological importance of this fungus, its mitochondrial genome has not been yet available.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of Class 3 endophyte species within the same host and different forests stands can be quite distinct [86,87]. Equally, the same endophytic species have been reported to occupy several and diverse plant hosts [86,[88][89][90][91][92].…”
Section: Nature Of Fungal Endophytesmentioning
confidence: 99%
“…In Pinaceae, the dominant endophytic fungal species documented belong to the classes Leotiomycetes, Dothideomycetes and Sordariomycetes [20,86,[128][129][130][131]. The frequency is extremely high in aerial parts of trees, but the studies have shown that for foliar endophytes, a relatively small number of endophyte species dominate the fungal communities [20,91,108,110,[132][133][134].…”
Section: Aerial Endophytesmentioning
confidence: 99%
“…Due to its unspecific mycoparasitism activity, C. rosea has been widely studied as a biocontrol agent of several important fungal plant pathogens [1, 6]. In addition, this species, and others in the genus, are known to be symptomless colonizers (or endophytes) of various plants, including woody species [1, 22, 23].…”
Section: Discussionmentioning
confidence: 99%